Sodium nitroprusside is effective in preventing and/or reversing the development of schizophrenia‐related behaviors in an animal model: The SHR strain. (14th April 2018) - Diana, Mariana C.; Peres, Fernanda F.; Justi, Veronica; Bressan, Rodrigo A.; Lacerda, Acioly L. T.; Crippa, José Alexandre; Hallak, Jaime E. C.; Abilio, Vanesssa Costhek
Summary: Aims: The treatment of schizophrenia with antipsychotics is still unsatisfactory. Therefore, the search for new treatments and prevention is crucial, and animal models are fundamental tools for this objective. Preclinical and clinical data evidence the antipsychotic profile of sodium nitroprusside (SNP), a nitric oxide (NO) donor. We aimed to investigate SNP in treating and/or preventing the schizophrenia‐related behaviors presented by the spontaneously hypertensive rats (SHR) strain. Methods: Wistar rats (WR) and SHRs were submitted to two schemes of treatment: (i) a single injection of SNP or vehicle in adulthood; (ii) a long‐term early treatment from 30 to 60 postnatal day with SNP or vehicle. The following behaviors were evaluated 24 hours after the acute treatment or 30 days after the long‐term treatment: locomotion, social interaction, and contextual fear conditioning. Results: Spontaneously hypertensive rats presented hyperlocomotion, decreased social interaction, and impaired contextual fear conditioning. Single injection of SNP decreased social interaction in both strains and induced a deficit in contextual fear conditioning in WR. Oppositely, early treatment with SNP prevented the behavioral abnormalities in adult SHRs without promoting any effects in WR. Conclusion: Our preclinical data point to SNP as a preventive and safe strategy with a broad range of effectiveness to the positive, negative, and cognitive symptoms of schizophrenia.